Nephrologic abnormalities in neonatal asphyxia at Cipto Mangunkusumo Hospital, Jakarta - Idham Amir; Vera M Manoe; Taralan Tambunan (Indonesian Pediatric Society Publishing House, 2016)
Introduction Neonatal asphyxia is still the leading cause of high morbidity and mortality in developed countries, as well as in devel- oping countries including Indonesia. As a response to asphyxia, renal hypoxia occurs which is initially temporary, but if persisting, can cause permanent damage to the cortex and medulla. Objective The purpose of this study was to determine the nephrologic abnormalities in neonatal asphyxia at Cipto Mangunkusumo Hospital. Methods This was a cross sectional descriptive study conducted in the Division of Neonatology, Cipto Mangunkusumo Hospital from August until November 2002. Neonates with congenital malforma- tion were excluded. Results The study showed that the incidence of nephrologic ab- normalities in neonatal asphyxia based on Apgar scores at 1, 5, and 10 minutes were 65/100, 26/33, and 5/6, respectively. The risk of nephrologic abnormalities was not statistically different in se- vere asphyxia compared to moderate asphyxia. Severe asphyxia at 1 minute Apgar scores was correlated with the occurrence of oliguria. Conclusion In asphyxiated newborn, it is very important to inves- tigate the possibility of nephrologic abnormalities